Legal Protection Against Sekaa Sidha Angklung Gamelan Equipment Theft Work by Tabanan Police - Sukmayanti, Made Sinthia; Sudirga, I Made; Novelin, Tania (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The aim of writing this article is to explain legal protection and obstacles to the theft of Sekaa Sidha Karya angklung gamelan equipment by the Tabanan Police. This research uses an empirical legal research method with a sociological approach, data obtained from field research directly at the location through interviews with informants and respondents to obtain primary data, while the literature obtains secondary data. The results of the research explain that legal protection for cases of theft of Sekaa Sidha Karya angklung gamelan equipment by the Tabanan Police is through preventive and repressive legal protection in accordance with the provisions of Articles 13, 14, 15 and 16 of Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia. Obstacles that occur in law enforcement regarding the theft of angklung gamelan equipment include not finding evidence, the absence of witnesses and supporting facilities at the crime scene, delays in reporting, and a lack of community cooperation with the police.